Caracterização morfológica e citogenética de sementes e plântulas de algumas espécies de plantas tóxicas - Andrade, Débora Aparecida Verde de [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
Este trabalho teve como objetivo caracterizar morfologica e citogeneticamente as especies de plantas toxicas: Crotalaria lanceolata E. Mey., Ricinus communis L., Cassia occidentalis L. , Canavalia ensiformis D.C. e Amaranthus spinosus L.. Para a morfologia utilizou-se sementes e plantulas que foram esquematizadas com auxilio de estereomicroscopio equipado com camara clara.Para a citogenetica utilizou-se pontas de raizes, hidroxiquinoleina e coloracao Giemsa. Crotalaria lanceolata E. Mey. apresenta sementes com variados tons de castanhos. A germinacao e epigea e fanerocotiledonar. O embriao e cotiledonar e o endosperma mucilaginoso. Apresenta numero cromossomico 2n = 16 cromossomos, com comprimento medio geral de 3,340 Êm } 0,689. Ricinus communis L. possui sementes com testa mesclada em tons castanhos, com caruncula visivel localizada na parte inferior da semente, germinacao epigea e fanerocotiledonar.O embriao e cotiledonar e o endosperma oleaginoso. O numero cromossomico 2n = 10 cromossomos, com comprimento cromossomico medio de 1,123 Êm } 0,327. Cassia occidentalis apresenta sementes com tons marrom-escuro, embriao cotiledonar e endosperma mucilaginoso. A germinacao e epigea e fanerocotiledonar. Possui 2n = 26 cromossomos com comprimento cromossomico medio e de 1,672 0,400. Canavalia ensiformis D.C apresenta sementes com uma coloracao branca e lignificada, embrião cotiledonar e endosperma mucilaginoso. A germinacao e do tipo epigea e fanerocotiledonar. Apresenta numero cromossomico 2n = 22 cromossomos com comprimento medio de 1,388 Êm 0,249......

This work had as objective to characterize morphologic and citogenetics some species of toxic plants: Crotalaria lanceolata E. Mey., Ricinus communis L., Cassia occidentalis L., Canavalia ensiformis D. C. and Amaranthus spinosus L.. For the morphological studies were used seeds and seedlings that were schematized with of stereomicroscoppe equipped with camera lucida. The cytogenetic already used points of rootses, Hidroxiquinoleina and Giemsa coloration. Crotalaria lanceolata E. Mey. present seeds with varied tones of chestnut . Its germination is phanerocotyledonar and epigeous. The seeds are kidney shaped and the embryo is cotyledonary with a mucilaginous endospermic. They present chromosome number 2n = 16 chromosomes, with general medium length of 3,340mm l 0,689. Ricinus communis L. presents seeds with forehead several mixed many tones chestnut, wich visible caruncula located in the inferior part of the seed, germination is phanerocotyledonar and epigeous. The seeds are kidney shaped and the embryo is cotyledonary and an oleaginous endospermic. Its chromosome number is 2n = 10 chromosomes, with length medium chromossomic of 1,123mm l 0,327. Cassia occidentalis presents seed with tones brown-darkness whose interior presents an embryo is cotyledonary and a mucilaginous endospermic. Its germination is phanerocotyledonar and epigeous. The evaluation cytogenetic shows us 2n = 26 chromosomes with length medium chromossomic are of 1,672mm l 0,400. Canavalia ensiformis D.C presents seeds with a white coloration and lignification. In its interior it is located an embryo cotyledonary... (Complete abstract, click electronic access below)
Keywords: Botânica - Morfologia; Plantas venenosas - Semente; Plantas venenosas - Citogenética; Plântula; chromosomes; Citogenetic; Morphology; Toxic plants